Comparative analysis of the visualization of small files using digital and conventional radiography Análise comparativa da visualização de limas de fino calibre, usando a radiografia digital e a convencional - Sandra Regina Boarin Pace; Sandra Márcia Habitante (University of São Paulo, 2005)
The present work was designed to carry out a comparative analysis of the visualization of small files using digital and conventional radiographs. Forty maxillary molars inserted in human skulls were used; Maillefer K-files #06, #08, #10 and #15 were inserted in the mesiobuccal canals and measured at 0.5mm beyond and 1.5mm before the tip with 0.5-mm intervals, in order to allow five professionals to observe whether the files were at the limit, before or beyond the foramen when visualized on conventional radiographs taken on Insight Kodak film (Eastman Kodak, Rochester, NY, USA) and with the RVG digital system (Trophy). Based on the results obtained, the conclusions were: with the two systems it was possible to visualize #06 K-files in nearly 60% of the evaluated cases; for the others, #08, #10 and #15 K-files, visualization was higher with both radiographic systems, achieving 82% of correct visualization for #15 K-files with the conventional system. The differences between the results of the two systems studied - conventional (Insight film, Kodak F-speed) and last generation digital (RVG - Trophy) radiographs - were not statistically significant according to the Student's t test. OBJETIVO: O objetivo deste trabalho foi comparar a visualização de limas de fino calibre usando as radiografias digital e convencional. MATERIAL-MÉTODO: Para tal, foram utilizados quarenta dentes molares superiores inseridos em alvéolos de crânio seco, com limas Maillefer tipo K de calibre #06, #08, #10 e #15, em canais mésio-vestibulares, mensurados de 0,5 mm além ápice a 1,5 mm aquém do ápice com intervalos de 0,5 mm, de forma que cinco avaliadores pudessem observar se as limas estavam no limite, aquém ou além do forame em radiografias convencionais com filme Insight Kodak (Eastman Kodak, Rochester, NY, USA) e sistema digital RVG (Trophy). CONCLUSÃO: Diante dos resultados obtidos concluiu-se que nos dois sistemas foi possível visualizar as limas #06 em cerca de 60% dos casos avaliados, para as demais limas - #08, #10 e #15-, a visualização foi superior em ambos os sistemas radiográficos, chegando a 82% de acertos para as limas #15 no sistema convencional. As diferenças entre os resultados dos dois sistemas estudados - radiográfico convencional (filme Insight, F speed) e digital (RVG - Trophy) de última geração - não foram estatisticamente significativas, segundo o teste t-Student.